Action of wheat’s genetic systems in depend on way of aluminum entrance into plant - E. M. Lisitsyn; O. A. Amunova (Аграрная наука Евро-Северо-Востока, 2017)
Estimation of influence of root and leaf input of aluminum into plants of spring soft wheat on activity of genetic systems of adaptivity, attraction, and micro-distribution of photosynthates were conducted under field conditions of Kirov region in 2014.. .2016. The estimation was done using graphs of orthogonal regression in co-ordinate systems “ear mass - straw mass” and “grain mass - chaff mass”. Changes in activity of the genetic systems differ quantitatively and qualitatively at different ways of aluminum ions’ impact. At varieties Vyatchanka, Magistral’naya 1, Svecha, Tumenskaya 80, and Estivum V313 top-dressing with 1.5 mM aluminum sulfate decreased activity of genetic system of micro-distribution. At varieties Bazhenka, Legenda, Sibirskaya 14, and Estivum 155 this treatment leads to re-distribution of photosynthates into economically useful part of ear. Activity of genetic systems of adaptivity and attraction was increased at varieties Magistral’naya 1, Svecha, Sibirskaya 14, and Estivum V313. Soil aluminum (211 mg/kg) increased effectiveness of action of genetic system of micro-distribution at varieties Altayskaya 80, Karabalykskaya 98, Legenda, Line 3691h, Estivum 155, and AC Taber. Varieties Altayskaya 80, Legenda, Tulajkovskaya 155, Tumenskaya 80, Estivum 155, and Nawra increased activity of genetic systems of adaptivity and attraction. These varieties could be used as sources for increasing of activity of the given genetic systems in breeding for Al-resistance. At varieties Legenda and Estivum 155 influence of soil aluminum leads to significant increase in activity of genetic systems of adaptivity and attraction, while top-dressing - decreased it. At varieties Svecha and Magistral’naya 1 there soil aluminum decreased activity of these systems, but top-dressing - increased. Only at variety Estivum 155 aluminum in both cases increased activity of genetic system of micro-distribution. All the rest varieties had opposite direction in change of activity of this system at different ways of stressor impact. Differences in varieties on level of aluminum resistance of root systems had not influence on activity of genetic system of micro-distribution at both ways of stressor’s impact. This fact indicates only weak genetic link between mechanisms of re-distribution of photosynthesis products within an ear of spring soft wheat and mechanisms of plant resistance against stress factors.